REFORMULASI TRADISI KEILMUAN PENDIDIKAN TINGGI ISLAM - Jannah, Siti Raudhatul (Al-Fikrah: Jurnal Kependidikan Islam, 2012)
The article attemps to explain about scientific tradition on Islamic Higher Education. It aims to propose a solution to undertake the problems that is faced by Islamic Higher Education. Scientific dichotomy give many negative effect on Islamic Higher Education not only in the world but also in our country. So, the writer finds that reformulation on Islamic Higher Education must be done. Keywords : Tradisi keilmuan, dikotomi, pendidikan tinggi Islam.